Starch films from a novel (Pachyrhizus ahipa) and conventional sources: Development and characterization - Lopez, Olivia Valeria (2012)
Biodegradable films from ahipa, cassava and corn native starches were developed by casting method and their physicochemical, mechanical and barrier properties were analyzed taking into account the different starch botanical sources. Filmogenic suspensions were prepared; their rheological behaviors were studied and all of them exhibited film-forming ability. However, mechanical assays demonstrated that unplasticized films were too rigid, limiting their technological applications. Thus, 1.5% w/w of glycerol as plasticizer was added to filmogenic suspensions and film flexibility and extensibility were improved, this effect was more significant for ahipa and cassava starch films. Furthermore, thickness, moisture content and water solubility of the developed films were increased when plasticizer was incorporated. Glycerol addition reduced film water vapor permeability and the lowest reduction corresponded to cassava starch films due to the high viscosity of its filmogenic suspensions. Plasticized starch films resulted to be UV radiation barriers; ahipa starch films had the lowest light absorption capacity and higher transparency than cassava and corn starch films. Dynamic-mechanical analysis indicated that plasticized films were partially miscible systems exhibiting two relaxations, one attributed to the starch-rich phase and the other to the glycerol-rich one. Likewise, it could be demonstrated that glycerol exerted a major plasticizing effect on ahipa starch matrixes.